Quality check of safety data sheets for plant protection product co-formulants: hazard classification and coherence of the information - Di Mare, Valerio; Garramone, Gaetano; Rubbiani, Maristella; Moretto, Angelo (La Medicina del Lavoro, 2017)
Background: Hazard classification of chemicals can be defined as a logic-mathematical operation aimed at identifying the type and severity of the inherent hazards of a substance or a mixture. Objectives: The purpose of this study was to evaluate, in 134 safety data sheets (SDSs): i) the hazard classification and ii) its coherence with sections 9 (physical-chemical properties), 11 (toxicological properties) and 12 (ecological properties) of the SDSs. Methods: Hazard classification and the information provided in sections 9, 11 and 12 of the SDSs have been evaluated against the criteria provided in annexes VI of the Dangerous Substance Directive, II and III of the Dangerous Preparations Directive, I and VI of the Regulation (EC) n. 1272/2008. Results: Most of the analyzed SDSs of substances (62%) was associated to non-classified chemicals (61.4%), although 19.6% of them should have been classified. By contrast, 59.4% of classified substances (representing 38.6% of analyzed ones) were wrongly classified. Fifty-four %, 54% and 67% of suggested substances hazard classification were in line with sections 9 (physical-chemical properties), 11 (toxicological properties) and 12 (ecological properties). Conclusions: The proportion of hazard classification mistakes in SDS was significant, suggesting the need of more qualified experts to derive classification. The introduction of an ad hoc evaluation team, managed by a single, qualified specialist, could represent a solution to ensure the needed improvement of SDSs quality.